Kinetics of Torque Teno Virus-DNA Plasma Load Predict Rejection in Lung Transplant Recipients. Issue 4 (April 2019) - Frye, Björn C.; Bierbaum, Sibylle; Falcone, Valeria; Köhler, Thomas C.; Gasplmayr, Markus; Hettich, Ina; Dürk, Thorsten; Idzko, Marco; Zissel, Gernot; Hengel, Hartmut; Müller-Quernheim, Joachim
Abstract : Background: Lung transplantation is the only therapeutic option in end-stage lung diseases; however, survival after transplantation is limited by acute and chronic rejection or infectious events being results of inappropriate immunosuppression. Torque Teno Viruses (TTVs) are ubiquitous DNA viruses in humans but not found to be causative for any disease. However, some reports suggest that TTV-DNA levels reflect the grade of immunosuppression with higher levels being found in more immunosuppressed individuals. Methods: We investigated the TTV-DNA levels in 34 lung transplant recipients within their first year after transplantation by quantitative real-time polymerase chain reaction. Clinical data were extracted from charts. Results: In accordance with previous results TTV-DNA levels increase after lung transplantation reaching a steady state after 3 months. The TTV-DNA levels were not correlated with immunosuppressive trough levels and a selective increase was not observed with other DNA viruses. In steady state TTV-DNA levels were significantly higher in patients with infectious complications compared to the group of patients without. Additionally, TTV-DNA levels decreased significantly before biopsy-proven rejection. Sensitivity of a 10-fold decrease in TTV-DNA levels for a subsequent rejection episode was 0.74 with a specificity of 0.99. Conclusions: In summary, TTV-DNA might be used as an additional tool to monitor immunosuppression in lung transplant recipients. Higher TTV-DNA levels reflect more intense immunosuppression, whereas the TTV-DNA kinetic (ie, decrease of TTV-DNA levels) indicate rejection. Abstract : Supplemental Digital Content is available in the text.